Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
The main purpose of establishing APS is to ensure that test performance aligns with their specific clinical goals. Analytical performance specifications serve multiple functions: as acceptance criteria to verify that in vitro diagnostic medical devices (IVD MD) meet regulatory and quality standards before market release; for external quality assurance assessments; for quality control, monitoring reagent lot-to-lot variability, and allowing preanalytical variation assessments in labs; and for guiding purchasing decisions by healthcare providers, reimbursement agencies, and both public and private insurers. Over the years, various systems and projects have been established to evaluate the current state of the art (Model 3) of IVD MD through external quality assurance (EQA). Different national and international EQA providers often use distinct acceptance criteria tailored to their organisational goals and local healthcare settings. Model 2, which relies on biological variation data, has been effectively supported by the European Federation of Clinical Chemistry and Laboratory Medicine's database and its interactive tools for calculating APS (www.biologicalvariation.eu). Nonetheless, debates continue about optimal APS setting methods and the most suitable models for different measurands and scenarios. To explore these issues further, workshops were held in Prague in 2023 and 2025. This report presents the expert presentations from the 2025 workshop, which exclusively focused on APS based on Model 1b.